Modern approaches to the assessment of orally inhaled products bioequivalence - E. S. Petrova; D. V. Goryachev; M. V. Petrov (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article analyses regulatory documents containing requirements for clinical (trials) documentation for orally inhaled products, including requirements for the demonstration of therapeutic equivalence of medicinal products for the treatment of bronchial asthma and chronic obstructive pulmonary disease in adults and children. The article summarises the main approaches to the assessment of inhalers equivalence. It also systematizes and describes dosage forms and inhalation devices, as well as the necessary stages of inhaler evaluation, looks into the methodology of conducting therapeutic equivalence studies with due regard to the therapeutic class of the drug, duration of its action and proposed nosology. The methodology includes requirements for the selection of the study population, study design and conditions, and recommendations for the selection of drug dose, study duration, primary and secondary efficacy and safety endpoints in the context of orally inhaled products.